Dose-Dependent Hyperkalemia Among Hospitalized, HIV-Infected Patients Receiving Sulfamethoxazole/Trimethoprim. Issue 9 (September 2020) - Caulder, Celeste R.; Kocherla, Caitlin S.; Qureshi, Zaina P.; Magagnoli, Joseph; Bookstaver, P. Brandon
Background: Sulfamethoxazole-trimethoprim (SXT) therapy is commonly used in HIV-infected patients and is associated with hyperkalemia and elevated serum creatinine (SCr).Objective: The purpose of this study was to examine the frequency of hyperkalemia and elevated SCr in hospitalized, HIV-infected patients receiving SXT.Methods: This was a retrospective, single-center cohort study. HIV-infected hospitalized patients receiving a minimum of 3 consecutive days of SXT were included. Patients were grouped according to high dose (≥10 mg/kg/d) and low dose (<10 mg/kg/d) trimethoprim. The primary end point was the frequency of hyperkalemia, severe hyperkalemia, and elevated SCr. Secondary end points included an evaluation of concomitant potassium-altering medications and concomitant nephrotoxic drugs.Results: A total of 100 consecutive patients were selected from all possible patients who met inclusion criteria. Overall, 47 patients experienced at least 1 adverse drug event (ADE) of either hyperkalemia or increased SCr, with 20 patients experiencing these ADEs in the low-dose group and 27 patients experiencing these ADEs in the high-dose group ( P = 0.229). The ADEs of hyperkalemia or increased SCr occurred after a shorter period (5.5 vs 8.7 days) in the high-dose group ( P = 0.049). Overall frequency of elevated SCr was 24% and of elevated serum K was 36%. Hyperkalemia requiring a therapeutic intervention occurred in 12 patients in the high-dose group compared with 2 in the low-dose group ( P = 0.009).Conclusion and Relevance: Rates of elevated SCr and hyperkalemia in hospitalized HIV-infected patients receiving SXT are significant. Hyperkalemia requiring intervention is more common in patients receiving high-dose SXT.